Endek Collaboration Unisex Top Clothes Design and Painting on Plain Fabrics - Dewi, Nur Warninda; Supriyatini, Sri; Sujana, I Wayan (Program Studi Seni Murni ISI Bali, 2023)
Entrepreneurship is the process of creating something different by devoting all of one' s t ime and energy accompanied by taking r isks f inancially, psychologically, socially, and receiving remuneration in the form of money and personal satisfaction. Agung Bali Collection as a partner in the Entrepreneurial MBKM activity has an important role in designing Endek Patchwork Collaborative Unisex Tops and Paintings on Plain Fabrics and in adding insight as well as introducing the author to new painting techniques using canting massage. The author performs several s tages in this production process such as; the stage of searching for materials, the s tage of making dress patterns, the s tage of cutting or cutting endek patchwork patterns, the stage of sketching paintings, painting designs usin g painting paint, the packaging s tage, and the marketing stage. The main target in marketing the production of painted clothing in collaboration with endek patchwork i s the Indonesian people, ranging f rom vulnerable teenagers to vulnerable adults aged 18 - 25 years. Trika. Collection i tself is a writer' s personal business, this business i s engaged in fashion and art by utilizing online media as a promotional medium, with plain t - shirts and endek patchwork as i t s main products. Plain t - shirts and endek patchwork are the raw materials for making products because the materials are s trong and environmentally friendly, and the use of endek patchwork in the Agung Bali Collection as a form of preserving t raditional culture and processing patchwork waste into goods wil l have high selling power.